KRITIK MATAN HADIS DI KALANGAN SAHABAT - Husen Maswara (TAHKIM, 2013)
The companions are known to be very enthusiastic listening hadith of the Prophet saw. However, sometimes there is a companion who heard hadith of the Prophet from other companions, but he silence it, because it was not in line with the view of other hadith or with her understanding of the Qur'an. If there is a companion who reject another companion history, or criticized in terms of matan, it does not mean the critics on the right side, because “the hadith criticism” has very broad field and a field of ijtihad. Of course, the results of criticism were adjusted to the view of concerned critics, or because he thinks are not in accordance with his understanding of the Qur'an, common sense, or assunnah (more saheeh). But there are other companions who disagreed. Keywords: Hadith criticism, matan hadith, validity level of hadith